Role of libraries in science and technology - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
For any inauguration you start by saying that you are extraordinarily pleased to be here to laboratory. One has only to read memoirs of inaugurate. I would like to submit this time that I really feel very happy to do so.